Psychometric Properties of Brief Screening Tests for Alcohol Use Disorders during Pregnancy in Argentina - Mariana Beatriz López; Aldana Lichtenberger; Karina Conde; Mariana Cremonte (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Background Considering the physical, mental and behavioral problems related to fetal alcohol exposure, prenatal clinical guides suggest a brief evaluation of alcohol consumption during pregnancy to detect alcohol intake and to adjust interventions, if required. Even if any alcohol use should be considered risky during pregnancy, identifying women with alcohol use disorders is important because they could need a more specific intervention than simple advice to abstain. Most screening tests have been developed and validated in male populations and focused on the long-term consequences of heavy alcohol use, so they might be inappropriate to assess consumption in pregnant women. Objective To analyze the internal reliability and validity of the alcohol screening instruments Alcohol Use Disorders Identification Test (AUDIT), Alcohol Use Disorders IdentificationTest- Consumption (AUDIT-C), Tolerance, Worried, Eye-Opener, Amnesia and Cut-Down (TWEAK), Rapid Alcohol Problems Screen - Quantity Frequency (RAPSQF) and Tolerance, Annoyed, Cut-Down and Eye-Opener (T-ACE) to identify alcohol use disorders in pregnant women. Methods A total of 641 puerperal women were personally interviewed during the 48 hours after delivery. The receiver operating characteristics (ROC) curves and the sensitivity and specificity of each instrument using different cut-off points were analyzed. Results All instruments showed areas under the ROC curves above 0.80. Larger areas were found for the TWEAK and the AUDIT. The TWEAK, the T-ACE and the AUDIT-C showed higher sensitivity, while the AUDIT and the RAPS-QF showed higher specificity. Reliability (internal consistency) was low for all instruments, improving when optimal cut-off points were used, especially for the AUDIT, the AUDIT-C and the RAPS-QF. Conclusions In other cultural contexts, studies have concluded that T-ACE and TWEAK are the best instruments to assess pregnant women. In contrast, our results evidenced the low reliability of those instruments and a better performance of the AUDIT in this population.